PENGENDALIAN KUALITAS ROLL KERTAS DENGAN MENGGUNAKAN METODE FAILURE MODE AND EFFECT ANALYSIS (FMEA) DAN METODE FAULT TREE ANALYSIS (FTA) - Andrian, Nur Moh. Danang; Zaini, Ahmad; Azzam, Akhmad Fatikhul; Satoto, Handy Febri (TEKNIKA, 2023)
PT. Adiprima Suraprinta is a manufacturer engaged in the recycling of used paper into paper that has market value. PT. Adiprima Suraprinta is a company from the Jawa Pos Group and one of the largest companies in East Java engaged in the paper industry. This company was founded on November 11, 1994. PT. Adiprima is a company that uses a make to order system. There is a problem when the paper roll is placed in the finished material warehouse during the loading process, almost every time a tear occurs in the paper roll wrapping which causes the paper roll wrapping to tear. So it is necessary to improve quality during the wrapping process by identifying the factors that cause defects. This research was conducted to determine the type of defect that has the highest level of disability and the corrective efforts that must be made. In research it is known that there are 6 attributes that cause defects that occur in the finishing process and there are 3 attributes of defects with the highest RPN values ​​that are important to be followed up immediately by the company including Wrapped paper rolls (140), Torn Roll Sides (150), and Torn paper Rolls ( 105).